2021
DOI: 10.1007/s00535-021-01793-0
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich alpha-2 glycoprotein is a potential biomarker to monitor disease activity in inflammatory bowel disease receiving adalimumab: PLANET study

Abstract: Background This multicenter prospective study (UMIN000019958) aimed to evaluate the usefulness of serum leucin-rich alpha-2 glycoprotein (LRG) levels in monitoring disease activity in inflammatory bowel disease (IBD). Methods Patients with moderate-to-severe IBD initiated on adalimumab therapy were enrolled herein. Serum LRG, C-reactive protein (CRP), and fecal calprotectin (fCal) levels were measured at week 0, 12, 24, and 52. Colonoscopy was performed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 27 publications
1
39
4
Order By: Relevance
“…Moreover, in some diseases like UC, IL-6 does not play a major role as CRP and SAA often remain at physiological levels [ 30 ]. Thus, the development of novel biomarkers represents an urgent clinical need for the early diagnosis and management of some inflammatory diseases and LRG1, being regulated by multiple pro-inflammatory cytokines, stands as a very promising candidate [ 160 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, in some diseases like UC, IL-6 does not play a major role as CRP and SAA often remain at physiological levels [ 30 ]. Thus, the development of novel biomarkers represents an urgent clinical need for the early diagnosis and management of some inflammatory diseases and LRG1, being regulated by multiple pro-inflammatory cytokines, stands as a very promising candidate [ 160 ].…”
Section: Reviewmentioning
confidence: 99%
“…Sinzaki et al conducted a prospective study (PLANET study) to investigate the usefulness of LRG as a monitoring biomarker for IBD. Serum LRG levels decreased with improved clinical and endoscopic outcomes during ADA therapy [132]. In a PLANET sub-study, Yanai et al showed that LRG could be a marker for predicting ADA trough levels in ADA-treated patients with CD and UC.…”
Section: Evaluation Of Disease Activity By Lrgmentioning
confidence: 99%
“…Yoshimura et al reported that serum LRG was lower in patients receiving anti-TNF-α agents than those in patients not receiving it [122]. The study by Sinzaki et al suggests that LRG may help monitor disease activity even after anti-TNF-α agents [132]. Yasutomi et al reported that in patients with UC, the area under the curve (AUC) of LRG in patients who received anti-TNF-α agents was not superior to that of patients who did not receive it.…”
Section: Effects Of Anti-tnf-α Agents On Lrg Levelsmentioning
confidence: 99%
“…Serum LRG exerted its superiority to mucosal healing in ulcerative colitis rather than C-reactive protein levels (Shinzaki et al, 2017). Serum LRG1 could also act as a useful biomarker to monitoring disease activity of inflammatory bowel disease during anti-TNF treatment (Shinzaki et al, 2021).…”
Section: Part Eight: Lrg1 Involved In Immune Diseasesmentioning
confidence: 99%